Clinically relevant transmitted drug resistance to first line antiretroviral drugs and implications for recommendations. - Susana Monge (Public Library of Science (PLoS), 2014)
Background The aim was to analyse trends in clinically relevant resistance to first-line antiretroviral drugs in Spain, applying the Stanford algorithm, and to compare these results with reported Transmitted Drug Resistance (TDR) defined by the 2009 update of the WHO SDRM list. Methods We analysed 2781 sequences from ARV naive patients of the CoRIS cohort (Spain) between 2007-2011. Using the Stanford algorithm "Low-level resistance", "Intermediate resistance" and "High-level resistance" categories were considered as "Resistant". Results 70% of the TDR found using the WHO list were relevant for first-line treatment according to the Stanford algorithm. A total of 188 patients showed clinically relevant resistance to first-line ARVs [6.8% (95%Confidence Interval: 5.8-7.7)], and 221 harbored TDR using the WHO list [7.9% (6.9-9.0)]. Differences were due to a lower prevalence in clinically relevant resistance for NRTIs [2.3% (1.8-2.9) vs. 3.6% (2.9-4.3) by the WHO list] and PIs [0.8% (0.4-1.1) vs. 1.7% (1.2-2.2)], while it was higher for NNRTIs [4.6% (3.8-5.3) vs. 3.7% (3.0-4.7)]. While TDR remained stable throughout the study period, clinically relevant resistance to first line drugs showed a significant trend to a decline (p = 0.02). Conclusions Prevalence of clinically relevant resistance to first line ARVs in Spain is decreasing, and lower than the one expected looking at TDR using the WHO list. Resistance to first-line PIs falls below 1%, so the recommendation of screening for TDR in the protease gene should be questioned in our setting. Cost-effectiveness studies need to be carried out to inform evidence-based recommendations.